Calcium Positively Mediates Blue Light-Induced Anthocyanin Accumulation in Hypocotyl of Soybean Sprouts - Hu, Gang; Yue, Xiaomeng; Song, Jinxue; Xing, Guipei; Chen, Jun; Wang, Haixia; Su, Nana; Cui, Jin (Frontiers in Plant Science, 2021)
Soybean sprouts are a flavorful microgreen that can be eaten all year round and are widely favored in Southeast Asia. In this study, the regulatory mechanism of calcium on anthocyanin biosynthesis in soybean sprouts under blue light was investigated. The results showed that blue light, with a short wavelength, effectively induced anthocyanin accumulation in the hypocotyl of soybean sprout cultivar “Dongnong 690.” Calcium supplementation further enhanced anthocyanin content, which was obviously inhibited by LaCl3 and neomycin treatment. Moreover, exogenous calcium changed the metabolism of anthocyanins, and seven anthocyanin compounds were detected. The trend of calcium fluorescence intensity in hypocotyl cells, as well as that of the inositol 1,4,5-trisphosphate and calmodulin content, was consistent with that of anthocyanins content. Specific spatial distribution patterns of calcium antimonate precipitation were observed in the ultrastructure of hypocotyl cells under different conditions. Furthermore, calcium application upregulated the expression of genes related to anthocyanin biosynthesis, and calcium inhibitors suppressed these genes. Finally, transcriptomics was performed to gain global insights into the molecular regulation mechanism of calcium-associated anthocyanin production. Genes from the flavonoid biosynthesis pathway were distinctly enriched among the differentially expressed genes, and weighted gene co-expression network analysis showed that two MYBs were related to the accumulation of anthocyanins. These results indicated that calcium released from apoplast and intracellular stores in specific spatial-temporal features promote blue light-induced anthocyanin accumulation by upregulation of the expression of genes related to anthocyanin synthesis of “Dongnong 690” hypocotyl. The findings deepen the understanding of the calcium regulation mechanism of blue light-induced anthocyanin accumulation in soybean sprouts, which will help growers produce high-quality foods beneficial for human health.